Dynamics of chiral cosmology. (9th September 2020) - Paliathanasis, Andronikos
Abstract: We perform a detailed analysis for the dynamics of chiral cosmology in a spatially flat Friedmann–Lemaître–Robertson–Walker Universe with a mixed potential term. The stationary points are categorized in four families. Previous results in the literature are recovered while new phases in the cosmological evolution are found. From our analysis we find nine different cosmological solutions, the eight describe scaling solutions, where the one is that of a pressureless fluid, while only one de Sitter solution is recovered.